Transformasi Konsep Komodifikasi Audiens pada Platform Media Digital Youtube sebagai Pelanggengan Kapitalisme - Fitri Sarasati; Udi Rusadi; Kristina Nurhayati (Jurnal Public Relations (J-PR), 2025)
This study aims to examine how audience commodification manifest within the Youtube ecosystem as part of  contemporary digital capitalism. In the context of platform based social-media, user attention and behavioral data are no longermade by products but have become primary commodities traded through targetd advertising systems. This study using a qualitative descriptive approach with a systematic litearure review method. The study integrates Dallas Smyhte’s audience commodity theory with contemporary frameworks such as survelillance capitalism and platform capitalism. Findings indicate that Youtube not only capture user attention but actively contructs micro-audience through algorithmically personalized behavoral data. Commodification extends beyond attention to include affect and even personal life, particularly evident in domestic micro-celebrity content. The study concludes that users function as unpaid digital laborers, while platforms maintain dominant control over value extraction and distribution. The research recommends strengthening digital critical literacy, ensuring algorithmic transparency, and fostering alternative platform development as collective strategies to counter the explitative logic of data capitalism.